Le determinanti dell’ecoinnovazione nelle pmi innovative: prospettive teoriche ed evidenze empiriche - Passaro, Renato; Scandurra, Giuseppe; Thomas, Antonio (Piccola Impresa / Small Business, 2020)
The exponential growth of the sensitivity of the community towards environmental issues and the awareness of environmental risks has led companies to coherently adapt to environmentally sustainable development their productive processes and products. In order to accelerate these processes, a flourishing international research stream that investigates the determinants that underlie the adoption of eco-innovations among firms has emerged. In light of the above objective, this paper aims to identify the level of dissemination of eco-innovations and the determinants that support their adoption within a specific population of Italian SMEs, the innovative SMEs introduced by law 33/2015. The results obtained show that a large part of the companies investigated show a high sensitivity towards eco-innovation issues; in particular, under the pressure of customers and final consumers. The choice to follow the principles of eco-compatibility, however, turns out to be dictated above all by factors of an individual nature, whereas, in the absence of an exhaustive public intervention, firms are still unable to perceive the economic advantages connected with the adoption of eco-innovations; from the image improvement, to the profitability increase.